Produksi Dan Ekstraksi Inhibitor Alfa Glukosidase Dari Isolat Aktinomiset Jp-3 - Pujiyanto, Sri; Ferniah, Rejeki Siti; S, Sunarno (Bioma : Berkala Ilmiah Biologi, 2015)
Alpha-glucosidase inhibitors are compounds that can prevent the digestion of complex carbohydrates into glucose, so potentially used as a diabetes drug. This study aims to examine the production and extraction of alpha-glucosidase inhibitor compound from Isolate Aktinomiset JP-3 from the sea. The supernatant obtained from the culture of the JP-3 isolate was extracted using various solvents to obtain the active compound. The solvents used were chloroform, methanol, and ethyl acetate. An assay of inhibitor activity of the Î±-glucosidase using p-nitrophenyl Î±-D-glucopyranoside substrate. The activity of the enzyme is measured based on the absorbance of p-nitrophenol produced from the breaking reaction of the substrate. The results showed that extraction of alpha-glucosidase inhibitor compound with ethyl acetate yielded extract with highest inhibitor activity.Â Keywords: alpha-glucosidase inhibitors, actinomycetes, diabetes, extraction, fractionation